De la «forest gasta» al «lignum crucis». Edició d’un poema anònim del segle XIV - Pujol, Josep (Caplletra. Revista Internacional de Filologia, 2015)
The text edited is an extant fragment, copied by the end of the XIVc and now kept in the Library of the monastery of Montserrat, of a medieval Cançoner written in the occitan-catalan language normally used by Catalan poets of the period. This rare sample shows the transference to poems written in the vernacular, of the symbolism related to the Cross, otherwise characteristic of Latin medieval hymnology. The author traces some parallellism with a poem by Peire Cardenal.